Dual Pathology in a Patient with Right Lower Quadrant Pain - Deutsch, Gary B. (Thieme Medical Publishers, 2012)
Meckel diverticula are remnants of the omphalomesenteric duct. They have 2% incidence in the general population, are usually asymptomatic, and tend to be diagnosed incidentally. The generally held principle had been that asymptomatic cases do not require resection, as exemplified by a 2008 systematic review of over 200 studies. However, a recent series reported an increased risk of malignancies, and recommended mandatory resection. We present a case of Meckel diverticulitis with concurrent infiltrative appendiceal carcinoid in a patient with right lower quadrant pain.